Ultrastable Imine‐Based Covalent Organic Frameworks for Sulfuric Acid Recovery: An Effect of Interlayer Hydrogen Bonding. Issue 20 (19th April 2018) - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul
Abstract: A rapid and scalable synthesis of six new imine‐linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2 SO4 (18 m ), conc. HCl (12 m ), and NaOH (9 m ). This is because of the presence of strong interlayer C−H⋅⋅⋅N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (−C=N−) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self‐standing, and crack‐free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as‐synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm −2  h −1  bar −1 ) and acetone (260 Lm −2  h −1  bar −1 ). Abstract : The rapid and scalable construction of highly porous and crystalline imine‐linked covalent organic frameworks (COFs) with ultra‐high stability (H2 SO4 18 m, HCl 12 m, NaOH 9 m ) is presented. The chemical stability was examined regarding the presence of significant interlayer C−H⋅⋅⋅N H‐bonding among the adjacent COF layers, which protects and prevents imine (−C=N−) bond hydrolysis through the steric and hydrophobic environment.